Factors Controlling In Situ Biogeochemical Transformation of Trichloroethene: Column Study. Issue 3 (8th August 2014) - Evans, Patrick J.; Nguyen, Dung; Chappell, Rick W.; Whiting, Kent; Gillette, John; Bodour, Adria; Wilson, John T.
Abstract In situ biogeochemical transformation involves biological formation of reactive minerals in an aquifer that can destroy chlorinated solvents such as trichloroethene (TCE) without accumulation of intermediates such as vinyl chloride. There is uncertainty regarding the materials and geochemical conditions that are required to promote biogeochemical transformation. The objective of this study was to identify amendments and biogeochemical conditions that promote in situ biogeochemical transformation. Laboratory columns constructed with plant mulch were supplemented with different amendments and were operated under varying conditions of water chemistry and hydraulic residence time. Four patterns of TCE removal were observed: (1) no removal, (2) biotic transformation of TCE to cis‐1, 2‐dichloroethene (cis‐1, 2‐DCE), (3) biogeochemical transformation of TCE without accumulation of reductive dechlorination products, and (4) mixed behavior where a combination of patterns was observed either simultaneously or over time. Principal coordinates analysis and analysis of variance (ANOVA) identified factors that promoted biogeochemical transformation: (1) high influent sulfate concentration, (2) relatively high hydraulic retention time, (3) supplementation of mulch with vegetable oil, and (4) addition of hematite or magnetite. The combination of the first three factors promoted complete sulfate reduction and a high volumetric sulfate consumption rate. The fourth factor provided a source of ferrous iron and/or a surface to which sulfide could react to form reactive iron sulfides. Many columns demonstrated either no TCE removal or a biotic TCE transformation pattern. Modification of column operation to include all four factors identified above promoted biogeochemical transformation in these columns. These results support the importance of the factors in biogeochemical transformation.